α-AMYLASE INHIBITION TEST OF ETHANOL EXTRACT OF MIANA RED TONGUE LEAVES (Solenostemon scutellarioides (L.) Codd) IN VITRO - Hartono, Dimas Rahmatullah Tri; Rukmi, MG. Isworo; Wulandari, Fitri (Jurnal Ilmiah Farmasi, 2025)
Background: Hyperglycemia occurs due to an increase in blood glucose levels, making them higher than the normal range, which is a sign of diabetes mellitus. One therapeutic approach for DM is inhibiting enzymes that convert carbohydrates into glucose. Coleus (S. scutellarioides (L.) Codd), an ornamental plant, is believed to have antihyperglycemic effects due to its phenolic phytochemicals.Objective: To determine the phytochemical content and antihyperglycemic activity of 70% ethanol extract of coleus leaves through α-amylase enzyme inhibition.Method: The leaves were characterized and tested qualitatively for phytochemical content using the test tube method. The extract was prepared using maceration with 70% ethanol, followed by thin-layer chromatography (TLC). The 200-ppm extract was tested for α-amylase enzyme inhibition, with acarbose as a positive control. Statistical differences were analyzed using the t-test method.Results: The herbarium specimen of coleus leaf was shown to contain flavonoids, tannins, saponins, and steroids. The 200-ppm extract reduced the activity of the α-amylase enzyme by 61.03%, while the positive control (acarbose) reduced it by 92.16%.Conclusion: The coleus leaf extract contains active phytochemicals that may help lower blood glucose levels. At 200 ppm, the extract demonstrates potential as an antihyperglycemic agent through α-amylase inhibition.